Um estudo sobre a formação e atuação dos professores de química do município da Serra do Mel/RN - Costa, Antonia Valbia Siqueira (Universidade Federal Rural do Semi-Árido, 2018)
The present research aimed at the training and performance of the chemistry teachers of public schools in Serra do Mel / RN, besides understanding the application and results of methodologies used by them in order to favor student learning of the discipline. The methodology used in the research was given through the application of a questionnaire for both teachers and students. The opinion of teachers regarding their teaching methodology, what students think about the discipline and understand the motivation of difficulty and aversion that is noticeable to the contents of chemistry. Based on the data obtained, it was verified that the teachers present difficulties in working on new methodologies, experimentation and contextualization of the contents, alleging lack of resources, laboratories and time to prepare the classes. In relation to the students, it is perceived that they are unmotivated and find the discipline difficult to understand, since it is taught without connection with the reality of the same, limiting itself to mere reproduction of contents, application of formulas and necessity to decorate concepts. Based on the answers, it is possible to see the difficulties that teachers face to teach chemistry classes, because in addition to the absence of material resources such as laboratories, there is also a lack of previous knowledge of other disciplines necessary for relevant learning, problems those that are accentuated even more when teachers are not acting in the area of their formation.
Monografia
Keywords: Formação inicial; Serra do Mel; Química; Estudantes; Professor; Initial formation; Serra do Mel; Chemistry; Students; Teacher; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL